Mutações Infernais: Uma análise comparativa das representações do Inferno n’A Divina Comédia e nos Evangelhos Apócrifos - Mestre, Beatriz (2024)
This article aims to compare a primitive Christian work, the Gospel of Nicodemus, and a work written during a time when Catholicism was facing some crises in Europe, The Divine Comedy, in order to reach a holistic perspective on the vision of Christians about Hell. In short, the proposed analysis highlights the evolution of the representation of the concept of Hell, from the first centuries of Christianity to Dante’s proposal, reflecting the changes in the medieval and Renaissance Christian perception of Hell.